Biomechanical comparison of different external fixator configurations for stabilization of supracondylar humerus fractures in children. (February 2016) - Hohloch, Lisa; Konstantinidis, Lukas; Wagner, Ferdinand C.; Strohm, Peter C.; Südkamp, Norbert P.; Reising, Kilian
Abstract: Background: Currently, closed reduction and percutaneous pinning are considered the treatment of choice for displaced supracondylar humerus fractures. However, indications exist for the use of external fixation with Schanz screws. In this in vitro study, we evaluate the biomechanical properties of a new variation for external fixation and compare them to an established construct. Methods: Twenty distal cadaver humeri (10 pairs) were allocated to 2 groups. The humeri of the first group were fixed by an external fixator consisting of Schanz screws and an oblique K-wire inserted from the distal radial cortex of the humerus, those of the second group were fixed by a new variation with the oblique K-wire inserted from the distal ulnar cortex of the humerus. Displacement and stiffness in static loading in internal and external rotation, as well as in extension and flexion were evaluated and compared. Findings: The variation of the external fixator of the second group proved to be statistically significantly superior to the variation of the first group in internal rotation loading (p > 0.05). In sagittal loading conditions and external rotation loading, the variations were equally stable (p > 0.05). There was no significant effect of the samples' bone density on displacement and stiffness values in any direction of loading. Interpretation: In cases of pediatric supracondylar humerus fractures when an external fixator is used for osteosynthesis, the insertion of an additional ulnarly inserted anti-rotation K-wire should be preferred to a radially inserted one as it reduces secondary displacement of the distal fragment.